Quantitative investigation of the decomposition of organic lithium ion battery electrolytes with LC-MS/MS. Issue 45 (25th May 2017) - Schultz, Carola; Vedder, Sven; Streipert, Benjamin; Winter, Martin; Nowak, Sascha
Abstract : A novel high performance liquid chromatography hyphenated to tandem mass spectrometry method for the separation and quantification of components from common organic carbonate-based electrolyte systems in lithium ion batteries was developed. Abstract : A novel high performance liquid chromatography (HPLC) hyphenated to tandem mass spectrometry (LC-MS/MS) method for the separation and quantification of components from common organic carbonate-based electrolyte systems in lithium ion batteries (LIBs) was developed. The method development included the quantification of organic electrolyte main components as well as selected aging products in LIBs. The separation of these compounds was optimized and the limits of detection (LODs), limits of quantification (LOQs) and recovery rates were determined. For the analysis of substances without commercially available standard substances, a quantitative approach was conducted. In this study, four different lithium hexafluorophosphate (LiPF6 )-based lithium ion battery (LIB) electrolytes were analyzed. These electrolyte samples were aged thermally (storage for two weeks at 60 °C and storage for two weeks at 60 °C with addition of 2 vol% water) and electrochemically (100 cycles at 2C at 20 °C and 60 °C and 100 cycles with higher upper cut-off potentials about 4.95 V, 5.20 V and 5.60 V vs. Li/Li + ). Thermal aging with the addition of water increased the amount of oligocarbonates in the electrolytes compared to thermal aging without the addition of water. Accordingly, the amounts of the main constituents decreased. After electrochemical aging at 20 °C, larger amounts of oligocarbonates and triethyl phosphate (TEP) were generated compared to electrochemical aging at 60 °C. Cycling with higher upper cut-off potentials led to the elevated formation of aging products in general.